A Power Factor Profile-Improved EV Charging System Using Bridgeless Buckboost-Cuk Converter - Tanmay Shukla; Narayan Prasad Patidar; Apsara Adhikari (International Transactions on Electrical Energy Systems)
This article presents a power factor profile-improved bridgeless buckboost-Cuk converter-fed battery charging system for electric vehicle applications. The conventional charging system does not use any power factor improvement stage, due to which the supply current harmonics are very high and violate IEC-61000-3-2 standard guidelines. To meet the international standard guidelines, a compact and efficient power factor-improved converter stage is necessary. The power factor-improved converter in the present work uses a fourth-order Cuk converter during negative semi-cycle and a second-order buckboost converter during positive semi-cycles of the supply voltage. The amalgamation of a second- and fourth-order converter in a bridgeless configuration reduces the system’s order concerning a bridgeless Cuk converter-based system and also eradicates the need for a diode-based bridge rectifier (DbBR). Due to the presence of an input side inductor, there is no requirement for an external filter like a bridgeless buckboost converter-based scheme. The input inductor in the present scheme performs twin action; it reduces harmonic disturbances in the mains current during the negative semi-cycle and also works with capacitor CP to filter harmonics and improve the mains current profile during the positive semi-cycle of the mains voltage. The power factor-improved converter in the present work is operated in discontinuous conduction mode (DCM). This eliminates the requirement for extra sensors compared to continuous conduction mode (CCM). The scheme also eliminates the need for two extra back-feed diodes which are generally required in bridgeless configuration loop completion during different semi-cycles of mains voltage. In the present scheme, the work of back-feed diodes is done by the anti-parallel inherent diodes of the switches. In the second stage, a high-frequency-operated flyback converter is used which not only boosts the battery current profile but also provides the electrical isolation between the supply side and load. This article also presents the detailed stability analysis and math modeling of the presented bridgeless buckboost-Cuk converter. The presented system is built on MATLAB/Simulink, and results are presented and discussed to validate the system performance.